INFLUENCE OF SHIFT WORK ON PSYCHOLOGICAL HEALTH AND MEMORY PERFORMANCE - rv, HemaMalini; N, Krishnamurthy; K, Prabhavathi; A, Saravanan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: In this modern society, 24 hrs continuous operation has become mandatory in many fields. Long and variable working hours for the shift workers lead to inadequate sleep. Hence, the objective of this study was to analyze the impact of rotating shift work on their psychological health and memory performance. Methods: 40 healthy male security guards (25-35 years) who did rotating night shifts at least for 1 year and 40 day workers (25-35 years) who did not do night shift in last 2 years were involved in the study. Psychological health status was assessed using Depression Anxiety Stress Scales (DASS) questionnaire. Their memory performances were assessed by digit symbol substitution test, letter cancellation test, word recall, and object recall. Data were analyzed using SPSS-20. Result: For assessing DASS questionnaire, Chi-square test was done. Among night shift workers, 60% significantly suffered from mild depression and 40% from moderate depression, 37.5% from mild stress, 52.5% from moderate stress, 45% from mild anxiety. 10% of the day workers suffered only from mild stress. Student's unpaired t-test showed a significant difference (p<0.05) for all the memory tests performed between night shift and day workers. Spearman correlation analysis was done and found to have a weak correlation between the memory performance and the psychological health status of the night shift workers. Conclusion: Rotating night shift workers who are prone to the circadian rhythm alteration suffer more from depression and stress than anxiety. There is deterioration in the memory performance and psychological health of the night shift workers when compared to day workers. Hence, psychological health status should be monitored regularly, and those who can cope up with night shift duties can continue, and others may be transferred to day shift. Keywords: Shift workers, Stress, Depression, Anxiety, Memory, Circadian rhythm.